Behavioral and Transcriptomic Fingerprints of an Enriched Environment in Horses (Equus caballus). - Léa Lansade; Mathilde Valenchon; Aline Foury; Claire Neveux; Steve W Cole; Sophie Layé; Bruno Cardinaud; Frédéric Lévy; Marie-Pierre Moisan (PLoS ONE, 2014)
The use of environmental enrichment (EE) has grown in popularity over decades, particularly because EE is known to promote cognitive functions and well-being. Nonetheless, little is known about how EE may affect personality and gene expression. To address this question in a domestic animal, 10-month-old horses were maintained in a controlled environment or EE for 12 weeks. The control horses (n = 9) lived in individual stalls on wood shaving bedding. They were turned out to individual paddocks three times a week and were fed three times a day with pellets or hay. EE-treated horses (n = 10) were housed in large individual stalls on straw bedding 7 hours per day and spent the remainder of the time together at pasture. They were fed three times a day with flavored pellets, hay, or fruits and were exposed daily to various objects, odors, and music. The EE modified three dimensions of personality: fearfulness, reactivity to humans, and sensory sensitivity. Some of these changes persisted >3 months after treatment. These changes are suggestive of a more positive perception of the environment and a higher level of curiosity in EE-treated horses, explaining partly why these horses showed better learning performance in a Go/No-Go task. Reduced expression of stress indicators indicated that the EE also improved well-being. Finally, whole-blood transcriptomic analysis showed that in addition to an effect on the cortisol level, the EE induced the expression of genes involved in cell growth and proliferation, while the control treatment activated genes related to apoptosis. Changes in both behavior and gene expression may constitute a psychobiological signature of the effects of enrichment and result in improved well-being. This study illustrates how the environment interacts with genetic information in shaping the individual at both the behavioral and molecular levels.